A dictionary for the modern clarinetist - Ellsworth, Jane (Dictionaries for the modern musician., 2015)
"In A Dictionary for the Modern Clarinet, scholar and musician Jane Ellsworth offers lovers of the clarinet the premiere reference book for information about this remarkable instrument. Containing over 400 terms, Ellsworth covers the clarinet's history (including both modern and historical instruments, common and rare), acoustics, construction, fingering systems and mechanisms, and techniques, as well as its more important performers, makers, and scholars"--Provided by publisher.